2021
DOI: 10.3390/v13102051
|View full text |Cite
|
Sign up to set email alerts
|

Virus Diseases of Cereal and Oilseed Crops in Australia: Current Position and Future Challenges

Abstract: This review summarizes research on virus diseases of cereals and oilseeds in Australia since the 1950s. All viruses known to infect the diverse range of cereal and oilseed crops grown in the continent’s temperate, Mediterranean, subtropical and tropical cropping regions are included. Viruses that occur commonly and have potential to cause the greatest seed yield and quality losses are described in detail, focusing on their biology, epidemiology and management. These are: barley yellow dwarf virus, cereal yello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 293 publications
(804 reference statements)
0
42
0
Order By: Relevance
“…Subsequent Australian studies found that widescale use of herbicides to remove grass and volunteer cereal hosts of WSMV and WCM before sowing wheat, had greatly decreased the number of seriously damaged crops (Coutts et al, 2014a;Jones, 2017). However, WSMV still causes considerable damage to early sown Australian wheat crops and in later sown situations where herbicide is applied too late to allow enough time for it to remove grass and volunteer cereal hosts effectively before wheat seedlings emerge (Coutts et al, 2008a(Coutts et al, , 2008b(Coutts et al, , 2014aFahim et al, 2010;Jones et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent Australian studies found that widescale use of herbicides to remove grass and volunteer cereal hosts of WSMV and WCM before sowing wheat, had greatly decreased the number of seriously damaged crops (Coutts et al, 2014a;Jones, 2017). However, WSMV still causes considerable damage to early sown Australian wheat crops and in later sown situations where herbicide is applied too late to allow enough time for it to remove grass and volunteer cereal hosts effectively before wheat seedlings emerge (Coutts et al, 2008a(Coutts et al, , 2008b(Coutts et al, , 2014aFahim et al, 2010;Jones et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Seed transmission in volunteer or sown wheat constitutes the principal means by which WSMV spreads to newly planted wheat crops in regions where wheat is sown in late spring after hot dry summers and harvested in autumn, as in south-west Australia. Its WCM vector spreads it over distance when infective mites are blown to healthy plants by the wind or locally from plant-to-plant when infected and healthy plants touch each other (Coutts et al, 2008b(Coutts et al, , 2014aJones, 2021;Jones & Barbetti, 2012;Jones et al, 2021). Comparisons between partial WSMV gene sequences led Dwyer et al (2007) to conclude that WSMV was introduced from the Pacific Northwest of the United States to Australia in contaminated wheat seed, and probably arrived 10-20 years before it was found in 2002.…”
Section: Introductionmentioning
confidence: 99%
“…These pathogens can cause two types of diseases: the first is barley yellow dwarfing virus (BYDV) (Belkahla and Lappiere, 2005). Whereas, the second type is the mosaic viruses named wheat streak mosaic virus (WSMV) represented by wheat streak mosaic virus (WSMV) and barley stripe mosaic virus (BSMV) (Jones et al, 2021). The BSMV pathogen, considered as the type member of the Hordeivirus genus, constitute a serious cereal pathogen, due to its efficient seed transmission and worldwide occurrence from United States (Carroll, 1980), Europe countries (Zarzyńska-Nowak et al, 2018), South Korea (Lim et al, 2016), Zambia (Kapooria and Ndunguru, 2004), Turkey (Köklü, 2004), Chile (Herrera, 2001) and Egypt (Hafez, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Both viruses are broadly distributed across the country including Queensland (Sharman et al 2021). PBMYV is primarily a pathogen of pulse legumes (Sharman et al 2021), whereas TuYV has a much broader natural host range including brassica, legume, ornamental and native plant species (Geering and Thomas 2022;Jones et al 2021). Earlier records of beet western yellows virus (BWYV) in Australia based on ELISA results are now considered erroneous due to the serological relatedness of this virus and TuYV: recent molecular analyses have revealed the presence of only TuYV in Australia (Filardo et al 2021;Jones et al 2021).…”
mentioning
confidence: 99%
“…PBMYV is primarily a pathogen of pulse legumes (Sharman et al 2021), whereas TuYV has a much broader natural host range including brassica, legume, ornamental and native plant species (Geering and Thomas 2022;Jones et al 2021). Earlier records of beet western yellows virus (BWYV) in Australia based on ELISA results are now considered erroneous due to the serological relatedness of this virus and TuYV: recent molecular analyses have revealed the presence of only TuYV in Australia (Filardo et al 2021;Jones et al 2021). Whole genome sequencing has shown that some isolates of PBMYV and TuYV have a recombinant ORF 5, although no biological differences due to the recombinations have been noted.…”
mentioning
confidence: 99%